Inside Front Cover: Volume 3 Issue 4. Issue 4 (20th December 2022) - Yiu, Chunki; Liu, Yiming; Zhang, Chao; Zhou, Jingkun; Jia, Huiling; Wong, Tsz H.; Huang, Xingcan; Li, Jian; Yao, Kuanming; Yau, Ming K.; Zhao, Ling; Li, Hu; et al.
Abstract : Inside front cover image : Cardiovascular diseases (CVDs) are fatal chronic diseases, where electrocardiography (ECG) monitoring could be a prominent solution for early diagnosis. In spite of available commercialized, multilead ECG devices, bulky formats, discontinuous monitoring, and no safety alarm system significantly limit their practical applications. Herein, we present a soft, and stretchable, three‐lead ECG device allowing continuous monitoring and wireless transmission of ECG signals. A newly developed organohydrogel patch with a strong adhesive ability ( 9.9 kPa) and higher conductivity ( 6.5 kΩ) is applied for high‐quality ECG signals collection. With a long operation duration (6.5 h) and wireless transmission distance (20.9 m), it could fulfill most of the daily applications. (DOI: https://doi.org/10.1002/smm2.1114 )